Organic Acid Formulation and Dip to Control Listeria monocytogenes in Hot Dogs - Lloyd, T.; Alvarado , C.Z.; Berrang, M.E. (International Journal of Poultry Science, 2012)
Commercially, hotdogs are handled after the cooking potentially causing contamination. Since consumers may eat hotdogs without reheating, the presence of Listeria Monocytogenes (LM) is a concern. In this study, treatments with organic acids in the raw product and as a post-cook dip were evaluated for their ability to suppress the growth of LM. Beef hotdogs were formulated with organic acids, cooked, cooled, inoculated with LM and then dipped in organic acid treatments. Treatments included: 1) Potassium Lactate (PL) in the formulation and Sodium Lactate (SL) in the dip, 2) PL in the formulation and SL with Sodium Diacetate (SD) in the dip, 3) SL and SD in the formulation and SL in the dip and 4) SL and SD in the formulation and SL and SD in the dip. Positive (inoculated) and negative (non-inoculated) controls were formulated with no organic acids and dipped in distilled water. All hotdogs were stored at 4°C and the number of LM was evaluated on day 0, 7, 14, 21, 28, 42 and 56. When compared to the positive control, all treatments resulted in significantly decreased LM numbers over time. The SL/SD with SL dip and SL/SD with SL/SD dip were the most effective treatments.